2021
DOI: 10.21203/rs.3.rs-656730/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptions on Impacts of Competition of Eucalypt Plantations with Other Land Uses on the Rural Livelihood in the Western Gurage Watersheds, Central-South Ethiopia

Abstract: Since recent years, conversions of croplands, grasslands or cash crop fields to eucalypt plantations are becoming common trends in Ethiopia. Reasons for the conversions are better return from eucalypt than crop farming. This study tried to assess the land use competition impacts of eucalypt plantations with other land uses in the Western Gurage Watersheds, Central-south Ethiopia. The specific objectives were to investigate households’ and experts’ perceptions on land use competition of eucalypt plantations; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Similarly, in Arsi Zone and in North Shewa Eucalyptus woodlot products contribute 28% and 0% of the household's total cash income, respectively (Mekonnen, 2012). Similarly, (Warkineh et al, 2021) reported that in Ethiopia, planting eucalypts have a significant contribution to household income.…”
Section: Contribution Of Eucalypts To the Rural Livelihoodsmentioning
confidence: 98%
“…Similarly, in Arsi Zone and in North Shewa Eucalyptus woodlot products contribute 28% and 0% of the household's total cash income, respectively (Mekonnen, 2012). Similarly, (Warkineh et al, 2021) reported that in Ethiopia, planting eucalypts have a significant contribution to household income.…”
Section: Contribution Of Eucalypts To the Rural Livelihoodsmentioning
confidence: 98%